2002
DOI: 10.1046/j.1469-0705.2002.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery score and perinatal outcome

Abstract: In high-risk third-trimester pregnancies, Doppler velocity waveforms of the uterine arteries can be evaluated using the uterine artery score disregarding the placental location. The uterine artery score possesses a high predictive value regarding adverse perinatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 17 publications
1
59
1
2
Order By: Relevance
“…However, its contribution in the identification and follow-up of high-risk fetuses has not been deeply studied. Different authors reported an increased risk for abnormal perinatal outcomes in presence of increased uterine arteries PI, despite having a normal UA-PI [23]. …”
Section: Discussionmentioning
confidence: 99%
“…However, its contribution in the identification and follow-up of high-risk fetuses has not been deeply studied. Different authors reported an increased risk for abnormal perinatal outcomes in presence of increased uterine arteries PI, despite having a normal UA-PI [23]. …”
Section: Discussionmentioning
confidence: 99%
“…However, number of studies proved that uterine artery Doppler useful even in the third trimester to identify adverse perinatal outcome. 7,8 The aim of present study was to investigate the association between third-trimester uterine artery Doppler assessment and adverse obstetric outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Previous uterine artery Doppler studies during the third-trimester examined pregnancies presenting with PE or fetal growth restriction and reported that the outcome was worse if impedance to flow was increased [20,21,22,23,24,25,26]. Two previous screening studies at 30-33 weeks' gestation examined 4,855 pregnancies and reported that at FPR of 5% screening by a combination of maternal characteristics and uterine artery PI or MAP detected 49 and 57%, respectively, of intermediate PE requiring delivery at 34-37 weeks and 37 and 49% of late PE with delivery at ≥38 weeks [27,28].…”
Section: Discussionmentioning
confidence: 99%